Contour Processing and 3-D Image Processing of Sea Beam Bathymetric Data - Asada, Akira (The International Hydrographic Review, 2015)
The Sea Beam system was installed aboard the survey vessel Takuyo (Nakanishi, 1985), in September 1983. It is currently used for continental shelf surveys, bathymetric surveys for predicting earthquakes and other survey activities. Besides these activities, we have been engaged in the development of a computerized system for drawing precise bathymetric charts based on digital Sea Beam data logged on magnetic tapes. So far we have completed two programs — one for drawing bathymetric contour charts aboard a survey vessel and the other for drawing bathymetric contour charts on shore. By means of the former program one can gradually draw depth contours covering the swath width of Sea Beam along the track of the survey vessel. The latter program enables one to draw very precise bathymetric charts through batch processing of all Sea Beam data of the area surveyed. Incorporated in the latter program are data processing steps to delete defective data, reduce dispersion of data, make a mesh system and adjust the mesh size according to the depth of water. Furthermore, taking advantage of the precision and high density of Sea Beam data, the author developed a three-dimensional image processing program to represent clearly the topography of the seafloor. We have used these programs with the Sea Beam data obtained in bathymetric surveys, and as a result have confirmed their practicability and validity.